Upaya Meningkatkan Kompetensi Pedagogik Guru Melalui Supervisi Akademik - Mestika Telaumbanua (JURNAL GLOBAL EDUKASI, 2020)
Abstract: This study aims to find out the right steps in carrying out academic supervision so that it can improve the teacher's pedagogical competence, especially in the learning process which will ultimately affect the improvement of the quality of education. The study was conducted in two cycles. The research subjects are principals and teachers. The school principal with his academic supervision actions, while the teachers of South Gunungsitoli 4 Middle School as objects and subjects in the provision of academic supervision treatment. Data collection techniques through classroom supervision with the stages of supervising teachers in the learning process and observing learning in class, to record important events related to research, especially when the learning process takes place. The results showed that the ability of teachers in the implementation of the learning process experienced an increase in the percentage at each stage, from the first cycle to an average of 63% (enough) and in the second cycle an average of 68% (good), an increase in the ability of teachers by 5% from cycle I. In detail there was a significant increase in the initial conditions of the school when compared to the final state in cycle II. The accuracy of teachers entering the classroom increased by 48%, the use of learning media increased by 32%, varied methods increased by 31%, and learning strategies increased by 36%. Keywords: pedagogical competence, academic supervision  Abstrak: Penelitian ini bertujuan untuk mengetahui langkah-langkah yang tepat dalam melaksanakan supervisi akademik sehingga mampu meningkatkan kompetensi pedagogik guru terutama dalam proses pembelajaran yang pada akhirnya akan berpengaruh terhadap peningkatan mutu pendidikan. Penelitian dilakukan dengan dua siklus. Subyek penelitian kepala sekolah dan guru. Kepala sekolah dengan tindakan supervisi akademiknya, sedangkan guru SMP Negeri 4  Gunungsitoli Selatan sebagai obyek sekaligus subyek dalam pemberian perlakuan supervisi akademik. Teknik pengumpulan data melalui supervisi kelas dengan tahapan mensupervisi guru dalam proses pembelajaran dan pengamatan pembelajaran di kelas, untuk mencatat kejadian-kejadian penting yang berhubungan dengan penelitian terutama pada waktu proses pembelajaran berlangsung. Hasil penelitian menunjukkan bahwa kemampuan guru dalam pelaksanaan proses pembelajaran mengalami peningkatan prosentase pada tiap tahapannya, dari siklus I mencapai rata-rata 63% (cukup) dan pada siklus II mencapai rata-rata 68% (baik), peningkatan kemampuan guru sebesar 5% dari siklus I. Secara rinci terjadi peningkatan yang signifikan terhadap kondisi awal sekolah bila dibandingkan dengan keadaan akhir pada siklus II. Ketepatan guru masuk ke dalam kelas meningkat 48%, pemanfaatan media belajar meningkat 32%, metode variatif meningkat 31%, dan strategi belajar meningkat 36%. Kata  kunci:  kompetensi  pedagogik,  supervisi  akademik